2018
DOI: 10.1002/asia.201801020
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Catalysis: A Powerful Technology for the Modification of Important Biomolecules

Abstract: Homogeneous catalysis plays an important and ubiquitous role in the synthesis of simple and complex molecules, including drug compounds, natural products, and agrochemicals. In recent years, the wide-reaching importance of homogeneous catalysis has made it an indispensable tool for the modification of biomolecules, such as carbohydrates (sugars), amino acids, peptides, nucleosides, nucleotides, and steroids. Such a synthetic strategy offers several advantages, which have led to the development of new molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 190 publications
(185 reference statements)
0
17
0
Order By: Relevance
“…Earlier in this section, the AIE or observed KIE has been expressed in eqn (1). Moreover, the computation of EIE and KIE is now clear from the previous paragraphs and equations.…”
Section: Apparent Isotope Effectsmentioning
confidence: 85%
See 1 more Smart Citation
“…Earlier in this section, the AIE or observed KIE has been expressed in eqn (1). Moreover, the computation of EIE and KIE is now clear from the previous paragraphs and equations.…”
Section: Apparent Isotope Effectsmentioning
confidence: 85%
“…21,22,25 The products of the H/ D-involved reaction are further analyzed by gas chromatography (GC), mass spectrometry (MS) and nuclear magnetic resonance (NMR) for quantitative and qualitative identification. Meanwhile, the experimental AIE can be calculated by eqn (1), where R H and R D denote the production rates with respect to H/D. Due to the experimental uncertainties and the nature of the reaction mechanism, it is not easy to distinguish the impacts from isotope swapping and further make a conclusion on the rate-determining step and mechanism of a reaction.…”
Section: Determination Of Isotope Effectsmentioning
confidence: 99%
“…On the other hand, homogeneous catalysts suffer from the aggregation of active catalytic sites. 8,[18][19][20] Hence, nanoparticles-based heterogeneous catalysis has been popularly used by researchers around the globe.…”
Section: Transition Metals As Catalystsmentioning
confidence: 99%
“…In 2015, R. Vadakkekara et al reported the synthesis of Au/Ag alloy nanoparticles supported on silica for oxidative esterification of benzaldehyde (Scheme 26). 19 The catalyst was prepared by sequentially adding AgNO3 and HAuCl4…”
Section: Au-ag/ Sio2 Nanoparticles Catalyzed Reactionsmentioning
confidence: 99%
“…Although homogeneous copper catalysts have made tremendous progress in the last few years, especially in the field of C–H activation, 13 they have some technological challenges such as the efficient separation of the catalyst from the reaction mixture and the recycling and reusing of the metal catalyst. 14 Environmental and industrial concerns make it essential to develop immobilized systems for the homogeneous Cu catalysts, which can circumvent their recovery and recycling properties. 15 In recent years, graphene-based materials have garnered intense interest because of their infinite planar lengths and nanoscale thicknesses.…”
Section: Introductionmentioning
confidence: 99%